2010
DOI: 10.1590/s0080-62342010000200034
|View full text |Cite
|
Sign up to set email alerts
|

Acidente ocupacional por material perfurocortante entre profissionais de saúde de um Centro Cirúrgico

Abstract: O acidente ocupacional por material perfurocortante constitui uma preocupação para instituições e trabalhadores de saúde, devido à elevada frequência de procedimentos invasivos, e a dinâmica do trabalho. Objetivou-se identificar a incidência dos acidentes, dos materiais envolvidos, dos fatores contribuintes e das condutas tomadas pós-acidente. Participaram de um estudo transversal 127 funcionários do centro cirúrgico. Registraram-se 23,6% (30/127) acidentes com envolvimento de agulha (73,3%), lâmina de bisturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
29

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 10 publications
(17 reference statements)
1
7
0
29
Order By: Relevance
“…10,17,18 In addition, it was shown that "irrelevance of the theme", "nonchalance" and "workload" also contribute to the underreporting of accidents. 23 At the same time, through the interviews, it is observed that they recognize that working with needlestick materials is already a risk, being the moment of handling these objects when usually the accidents occur. In accordance with this result, researches indicate that one of the factors related to the individual behavior of workers that favors the occurrence of accidents is the manipulation of needlestick materials.…”
Section: Carelessness and Improper Storage Of Needlestick Materialsmentioning
confidence: 99%
“…10,17,18 In addition, it was shown that "irrelevance of the theme", "nonchalance" and "workload" also contribute to the underreporting of accidents. 23 At the same time, through the interviews, it is observed that they recognize that working with needlestick materials is already a risk, being the moment of handling these objects when usually the accidents occur. In accordance with this result, researches indicate that one of the factors related to the individual behavior of workers that favors the occurrence of accidents is the manipulation of needlestick materials.…”
Section: Carelessness and Improper Storage Of Needlestick Materialsmentioning
confidence: 99%
“…By emphasizing the importance of the use of such equipment by health professionals, older people also demonstrate a concern with each other, justifi ed by the high rate of occupational accidents caused by the handling of sharp or piercing materials among health care workers (11) .…”
Section: [] Hospital Professionals Will Have To Use Gloves Masks mentioning
confidence: 99%
“…Quando o trabalhador reconhece a seriedade da questão, as cargas a que estão expostos e sua responsabilidade individual no contexto da prevenção abre-se um novo caminho, um repensar as práticas cotidianas, esse repensar pode ocorrer através do envolvimento de todos os profissionais por meios de seminários, reuniões clínicas, programa de educação permanente que promovam a construção e adoção de novas estratégias para a prevenção dos acidentes (Oliveira, Gonçalves, 2010).…”
Section: Discussionunclassified
“…Uma das formas de diminuir a subnotificação é a informação acerca da importância dos registros, alertar o trabalhador para o risco de ter sido infectado e a necessidade de respaldo legal no caso de afastamento do trabalho (Oliveira, Gonçalves, 2010).…”
Section: Estudo Realizado Em Um Centro Cirúrgico De Um Hospital Em Belounclassified